b - Gautier, Laurence (New Delhi : Cambridge University Press, 2024)
This book proposes a political history of Muslim universities in post-independence India, from 1947 to the 1990s. Based on a wide range of sources in English and in Urdu, it highlights the central role that these educational institutions played in the debates on national integration, secularism, minority rights and Muslim backwardness. After independence, Muslim universities found themselves at a critical juncture between central state authorities and India's Muslim population. As public and Muslim institutions, they were to participate in nation-building as much as in the development of the Muslim 'community'. By closely looking at the relation between these institutions and state authorities, the book teases out the ambiguities of the state's Muslim policy. It also examines, in turn, how university members responded to this policy and developed competing conceptions of Muslim identity and citizenship, which structured the wider public debates on Muslims' status in post-partition India.
Keywords: Group identity -- India -- History -- 20th century; Higher education and state -- India -- History -- 20th century; India -- History -- Partition